2009
DOI: 10.1111/j.1365-2095.2008.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison ofUlva clathrataand the kelpsMacrocystis pyriferaandAscophyllum nodosumas ingredients in shrimp feeds

Abstract: Three experimental diets were formulated to contain 33 g kg−1 seaweed meals, made of wild brown algae (kelps) Macrocystis pyrifera (MAC) and Ascophyllum nodosum (ASC) or of a cultivated green alga Ulva clathrata (ULVA). The diets were fed to juvenile white shrimp Litopenaeus vannamei (1.6 g) for 28 days. Loss of dry matter (LDM) and loss of protein (LP) after 1 hour immersion in seawater, and distilled water absorption (WA) were analyzed in the pelleted diets, as well as shrimp weight gain, feed intake, feed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 48 publications
2
43
0
8
Order By: Relevance
“…There is no complete study on the chemical composition of U. clathrata that we know of; Cruz-Suárez, Tapia-Salazar, Nieto-Lopez, Guajardo-Barbosa, and Ricque-Marie (2009) and Cruz-Suárez et al (2010) previously reported proximal and amino acid composition. The aim of the present study was to provide information on the proximal composition, dietary fibre, sugars, amino acids, fatty acids, carotenoids, and some minerals contents, of cultured green 0308-8146/$ -see front matter Ó 2011 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…There is no complete study on the chemical composition of U. clathrata that we know of; Cruz-Suárez, Tapia-Salazar, Nieto-Lopez, Guajardo-Barbosa, and Ricque-Marie (2009) and Cruz-Suárez et al (2010) previously reported proximal and amino acid composition. The aim of the present study was to provide information on the proximal composition, dietary fibre, sugars, amino acids, fatty acids, carotenoids, and some minerals contents, of cultured green 0308-8146/$ -see front matter Ó 2011 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…The continued growth of shrimp aquaculture is demanding increasingly higher amounts of feeds and, in this context, improved feeds and feeding strategies would optimize feed utilization. Because of their nutritional properties, several seaweed meals have been used as dietary supplements in shrimp feeds (Briggs & Funge-Smith 1996, Pen˜aflorida & Golez 1996, Cruz-Sua´rez et al 2009a). The chemical composition of macroalgae varies among species and environmental conditions; however, most are rich in nonstarch polysaccharides, vitamins, and minerals (Mabeau & Fleurence 1993, Wong & Cheung 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Three types of diet when provided to P. semisulcatus containing natural carotenoid sources like red pepper and marigold flower resulted in higher carotenoid accumulation in body tissues (Gocer et al, 2006). However research findings from Mexico also reported that feed incorporated with cultivated green alga Ulva clathrata significantly improved the body pigmentation of farmed shrimp L. vannamei (Cruz-Suarez et al, 2009).…”
Section: Resultsmentioning
confidence: 97%